an anthology, women's work is never done. - de Zegher, Catherine; Maiolino, Anna Maria; Roth, Moira; Pollock, Griselda; Horsfield, Craigie (MER.Paper Kunsthalle : Gent, 2014)
Nicodemus, Everlyn; Vicuna, cecilia; Hatoum, Mona; Janssens, Ann Veronica; Rosler, Martha; Spero, Nancy; Gallagher, Ellen; Maiolino, Anna Maria; Newman, Avis; Atkins, Anna; af Klint, Hilma; Kunz, Emma; Martin, Agnes; Gego; Hesse , eva; Tuerlinckx, Joëlle; Mehretu, Julie; Iglesias, Cristina; Shettar, Rajani; Ettinger, Bracha L.; Verhaeghe, Ria; Grzymala, Monika; De Keersmaeker, Anne Teresa, Wright, Juditg; Kot'atkova, Eva; Bloch, Pierrette; Gill, Simryn
boek